Thoracic-lumbar-sacral spine sagittal alignment and cranio-mandibular morphology in adolescents. (October 2019) - Piancino, Maria Grazia; Dalmasso, Paola; Borello, Fabio; Cinnella, Pasquale; Crincoli, Vito; Garagiola, Umberto; de Biase, Corrado; Tonni, Ingrid; Matacena, Giada; Deregibus, Andrea
Abstract: Purpose: The relationship between thoracic-lumbar-sacral spine sagittal alignment and craniofacial morphology is still controversial. Evidence-based results are difficult to obtain and scientific studies are inhomogeneous. The aim of this study was to investigate the difference of thoracic-lumbar-sacral spine posture and cephalometric values comparing two groups of subjects with different cranial structure in the sagittal plane. Methods: Eighty-one subjects were consecutively selected and divided into two groups, according to the orientation of the condyle-orbital plane (CoOr) with respect to the superior maxilla (SpP): Group1: 49 subjects 11.6 (2.1) years showing posterior-rotation of CoOr: SpP^CoOr ≤ −2°, −4.1°(2.1°); Group2: 32 subjects 12.9 (2.3)years showing anterior-rotation of CoOr: SpP^CoOr ≥ 2°, 3.7°(1.9°). Each patient underwent in blinding, Spinal Mouse recording and cephalometry of the skull. Results: Group1 showed a significant forward tilting of the spine 4.4°(1.8°) with respect to Group2 2.4°(1.3°) (p < 0.0001) and higher values related to the vertical dimension of the skull: higher maxillary divergency (p < 0.0001), steep occlusal plane (p < 0.0007), higher gonial angle (p < 0.001). Discussion: The results of this study showed a difference in the thoracic-lumbar-sacral spine inclination between groups with different craniofacial morphology. The achievement of this outcome is important to improve our multidisciplinary evaluation and treatment planning.